3D Printed SnSe Thermoelectric Generators with High Figure of Merit. Issue 26 (3rd June 2019) - Burton, Matthew R.; Mehraban, Shahin; Beynon, David; McGettrick, James; Watson, Trystan; Lavery, Nicholas P.; Carnie, Matthew J.
Abstract: Since the discovery of the record figure of merit (ZT) of 2.6 ± 0.3 in tin selenide (SnSe), the material has attracted much attention in the field of thermoelectrics. This paper reports a novel pseudo‐3D printing technique to fabricate bulk SnSe thermoelectric elements, allowing for the fabrication of standard configuration thermoelectric generators. In contrast to fabrication examples presented to date, this technique is potentially very low‐cost and allows for facile, scalable, and rapid fabrication. Bulk SnSe thermoelectric elements are produced and characterized over a wide range of temperatures. An element printed from an ink with 4% organic binder produces the highest performance, with a ZT value of 1.7 (±0.25) at 758 K. This is the highest ZT reported of any printed thermoelectric material, and the first bulk printed material to operate at this temperature. Finally, a proof‐of‐concept, all printed SnSe thermoelectric generator is presented, producing 20 µW at 772 K. Abstract : Bulk 3D printed SnSe thermoelectric elements are printed exhibiting an unprecedently high figure of merit for printed thermoelectrics, 1.7 at 758 K. The printing technique is exploited to fabricate the first printed SnSe thermoelectric generator. This novel printing technique opens a route to cheaply produce bulk thermoelectric generators, where generators can be printed to meet dimensional requirements of each application.